Quantifying inter-organelle membrane contact sites using proximity ligation assay in fixed optic nerve sections. (December 2021) - Ching, Jared; Osborne, Andrew; Eva, Richard; Prudent, Julien; Yu-Wai-Man, Patrick
Abstract: Membrane contact sites (MCS) play crucial roles in cell physiology with dysfunction in several MCS proteins being linked with neurological and optic nerve diseases. Although there have been significant advances in imaging these interactions over the past two decades with advanced electron microscopy techniques, super-resolution imaging and proximity-dependent fluorescent reporters, a technique to observe and quantify MCS in mammalian optic nerve tissues has not yet been reported. We demonstrate for the first time that proximity ligation assay (PLA), a technique already used in mammalian cell lines, can be used as an efficient method of quantifying inter-organelle contact sites, namely mitochondria-endoplasmic reticulum (ER) and mitochondria-late-endosomes, in mammalian optic nerve tissues treated with adeno-associated virus (AAV) gene therapy with wild-type or phosphomimetic (active) protrudin. PLA utilises complementary single-stranded DNA oligomers bound to secondary antibodies that hybridise and complete a circular piece of DNA when the primary antibodies of interest interact. These interactions can be detected by amplifying the circular DNA and adding fluorescent probes. We show that PLA is a useful method that can be used to quantify MCS in optic nerve tissues. We have found that upregulation of protrudin with gene therapy significantly increases the number of mitochondria-ER and mitochondria-Rab7-late endosomes contact sites in optic nerves.